A web r??dio escola como instrumento de educa????o, cultura e cidadania - Gon??alves, Aladim Lopes (2015)
The present research analyzes the study of radio education as a teaching tool and analyzes the use of the internet as template of transmission of its programming from Web Radio Escola, an educational radio service with webcast and whose target audience students, teachers, schoolmasters and school community. The radio was created by the Education Secretary of Parana State and it is presented as a new proposal approach to teaching children and adolescents, involving the historical force of educational radio and the new tools of communication and information technology to serve as a model broader on education. As a descriptive study of facts and phenomena observed in radio programming, as awakening to the use of new technologies in school and distortion with the teacher resistance to discuss educational tools of radio in the classroom. The data collection process and the information gathered in interviews and testimonials from people involved in the production of Web Radio Escola also provided information and important details for the composition of this research. The bibliographic support brought the necessary references and allowed to establish dialogues and debates on aspects of education, the use of new technologies and impacts on society. The study also discusses the integration of education and communication practices as a new social intervention and beyond the issues of participation and citizenship, which are also part of the theme of radio education. As result, this research rescues the social importance of radio education and recognizes its great potential in the convergence with the new technologies, indicating that the radio programming by the internet can bring new perspectives for education in the 21st century.